Adam Bede - Eliot, George, 1819-1880.; Gill, Stephen Charles (New York : Penguin Books, 1985)
Set in early nineteenth-century English countryside, an English squire yields to the temptations of an innocent country girl and crime, remorse, and suffering are the consequences.
Originally published in 1859.
Keywords: Carpenters -- Fiction; Infanticide -- Fiction; Women clergy -- Fiction; England -- Fiction; Didactic fiction; Love stories